1989
DOI: 10.1038/341164a0
|View full text |Cite
|
Sign up to set email alerts
|

The codon CUG is read as serine in an asporogenic yeast Candida cylindracea

Abstract: Deviations from the universal genetic code have been reported for several microorganisms. Termination codons are used for coding some amino acids in Paramecium, Mycoplasma or Tetrahymena, and in Escherichia coli, the UGA termination codon is used to code for selenocysteine. In mitochondria, the changes of sense codons to termination codons or to codons encoding other amino acids have also been reported. Here we report another example of divergence from the universal code, this time in a non-spore-forming yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(122 citation statements)
references
References 18 publications
4
117
1
Order By: Relevance
“…Similar observations were previously made in several Candida species [13,14] and Debaryomyces hansenii [15]. Unfortunately, we have not been able to identify the corresponding tRNA gene suggesting that it is present at a low copy number.…”
Section: Trnassupporting
confidence: 86%
“…Similar observations were previously made in several Candida species [13,14] and Debaryomyces hansenii [15]. Unfortunately, we have not been able to identify the corresponding tRNA gene suggesting that it is present at a low copy number.…”
Section: Trnassupporting
confidence: 86%
“…Assuming that a similar signalling cascade might exist in C. albicans and that the corresponding homologous genes could be expressed in S. cerevisiae despite the deviation from universal translation rules for some Candida species (32,60,69), we were able to isolate a complementing C. albicans homolog of the S. cerevisiae SLT2 gene, suggesting that a signalling cascade homologous to the Pkc1-controlled cascade of S. cerevisiae is functional in this opportunistic fungus. The isolated gene, named MKC1, replaced the function of SLT2 in S. cerevisiae null mutants by restoring growth and preventing autolysis at 37ЊC, thus showing that the Candida gene is expressed in Saccharomyces cells.…”
Section: Discussionmentioning
confidence: 79%
“…In Candida species, the codon CUG is known to be translated as serine instead of leucine by the tRNA CAG Ser responsible for this non-universal decoding (45,46). We previously reported that this tRNA CAG Ser can be aminoacylated not only with serine, but also with leucine to some extent in vitro as well as in vivo (47).…”
Section: Discussionmentioning
confidence: 99%